Analisis Peran Pemerintah dan Sektor Swasta dalam Pengembangan Pariwisata Halal: Studi Kasus di Indonesia dan Hong Kong - Ghozani, Sobi; Moh. Muslih; Hendri Hermawan Adinugraha (Sahmiyya: Jurnal Ekonomi dan Bisnis, 2024)
This research has discussed the role of the government and private sector in the development of halal tourism in Indonesia and Hong Kong. The main issue raised is how these two sectors support and develop halal tourism through various strategies and initiatives. This study aims to identify the strategy implemented, challenges faced and outcomes of the two sectors’ efforts to promote halal tourism. This research uses a comparative case study method with a qualitative approach. Data were collected through document analysis, stakeholder interviews, and field observations. The Public-Private Partnership (PPP) theory was used as a theoretical framework to evaluate the roles, responsibilities, and interactions between the public and private sectors in developing halal tourism. The results show that the governments in both regions play an essential role in promoting halal tourism through different policies and regulations. In Indonesia, halal certification is mandatory and regulated by the Halal Product Guarantee Agency (BPJPH), while in Hong Kong, halal certification is voluntary and conducted by independent agencies. The private sector also contributes significantly by providing Muslim-friendly services and facilities, such as halal-certified food and worship facilities. This study found that collaboration between the government and the private sector is crucial for the successful development of halal tourism. The strict regulatory approach in Indonesia and the voluntary approach in Hong Kong show that policy flexibility can deliver different positive outcomes according to the local cultural and market context. Sustainable halal tourism development requires strong government and private sector collaboration. Continued contributions from both sectors can accelerate the growth of halal tourism in the future. This research also provides practical recommendations to enhance public-private partnerships in halal tourism through effective training, education, and international promotion.